Asnaf Development Outcome: A Systematic Literature Review and Logic Model Development - Mohd Suffian Mohamed Esa; Hairunnizam Wahid; Salmy Edawati Yaacob; Abdul Hayy Haziq Mohamad (SAGE Open)
The objective of this Systematic Literature Review (SLR) is to review the impact of zakat distribution on the development of asnaf (zakat recipients), using a logical framework to analyze the relationships between zakat inputs, distribution processes, and outcomes. The study follows the PRISMA protocol, comprising four stages: identification, screening, eligibility, and inclusion. Out of 947 articles retrieved, 651 were excluded, and after a detailed review, 44 articles published between 2020 and 2024 in the fields of economics and management were selected. Quality appraisal was conducted using the Mixed-Method Appraisal Tool (MMAT), and thematic data extraction was done inductively, validated by two experts. Thematic data extraction was performed inductively, and validation was provided by two experts to ensure the relevance and accuracy of the findings aligned with a logic model. The findings highlight three key areas of asnaf development programs: economic, educational, and health dimensions, alongside innovation and digital technology applications. Although these programs show positive effects on behavior and contribute to poverty alleviation, some have produced mixed outcomes, indicating that improvements are still needed in the implementation of productive zakat. This study offers practical insights for policymakers by identifying effective strategies for managing inputs to generate outputs that align with desired outcomes. It also outlines key directions for future research, including the development of asnaf career programs for economic empowerment, evaluations of educational initiatives targeting asnaf children, and the integration of Conditional Cash Transfer (CCT) models to address poverty and behavioral challenges more effectively.